DESIGN AND DEVELOPMENT OF A FRANGIPANI FLOWER DRYING DEVICE BASED ON ARDUINO NANO - Krisna, I Kadek; Adnyana , I Gede; Antara, I Gede Made Yudi; Putra, I Dewa Putu Gede Wiyata; Ekayana, Anak Agung Gde (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Drying frangipani flowers (Plumeria) is vital for producing high-quality dried flowers, primarily used in incense production. Traditional sun-drying methods are inefficient and weather-dependent, often leading to inconsistent results and quality degradation. This study presents the design and development of a frangipani flower drying device using Arduino Nano, equipped with a heater, a fan, and thermocouple sensors for precise temperature control. The device was tested at two temperature setpoints, 45°C and 55°C, with a drying duration of 3 hours. Results showed that at 45°C, the device achieved a 40% weight reduction and produced flowers with moderate texture and aroma. At 55°C, the weight reduction increased to 68.8%, yielding flowers with superior texture, color, and fragrance, optimal for incense production. The temperature control system demonstrated high stability, with average deviations of less than 0.2°C across three sensors, ensuring uniform drying. Compared to traditional methods, the device improved drying efficiency by 30% and eliminated weather dependency. This cost-effective and practical solution enables frangipani flower collectors to enhance productivity and meet market demands consistently.